PENINGKATAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN TEMA 1 INDAHNYA KEBERSAMAAN KELAS IV SDN 1 JIMBUNG - Muhammad Feby Ulul Azmi (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2022)
Abstract : Improving Student Learning Outcomes Through the Use of Problem Based Learning Models in Learning Theme 1 The Beauty of Togetherness Class IV SDN 1 Jimbung. The background of this research is that the learning model used is not yet innovative in the learning process. Low student learning activities seen from students who are less active in the learning process because learning is still teacher-centered. The subject of this research is the fourth grade students of SDN 1 Jimbung for the academic year 2022/2023 with a total of 6 students. The data collected is qualitative data covering student learning activities and quantitative data covering student learning outcomes and classical learning completeness. This research is declared successful if student learning outcomes and student learning activities increase according to predetermined success indicators. The results of the first cycle research showed that students' learning completeness was 33.33% with a class average of 66.67. With the results obtained, researchers have not been able to meet the indicators of success. Therefore, the researchers made improvements in the second cycle so that the research results could increase. In cycle II, student learning completeness reached 66.67% with a class average of 75. With the results obtained, researchers have not been able to meet the indicators of success. Therefore, the researchers made improvements in the third cycle so that the research results could increase. In the third cycle, student learning completeness reached 83.33% with a class average of 88.33. Thus, it can be concluded that the Problem Based Learning model can improve student learning outcomes, class average, classical learning completeness, and learning activities IV at SDN 1 Jimbung.